Inside the Envelope: Endogenous Retrovirus-K Env as a Biomarker and Therapeutic Target - Nadeau, Marie-Josée; Manghera, Mamneet; Douville, Renée N. (Frontiers in Microbiology, 2015)
Due to multiple ancestral human retroviral germ cell infections, the modern human genome is strewn with relics of these infections, termed endogenous retroviruses (ERVs). ERV expression has been silenced due to negative selective pressures and genetic phenomena such as mutations and epigenetic silencing. Nonetheless, select ERVs have retained the capacity to be damaging to their host when reawakened. Much of the current research on the ERVK Env protein strongly suggests a causal or contributive role in the pathogenesis of various cancers, autoimmune and infectious diseases. Additionally, there is a small body of research suggesting that ERVK Env has been domesticated for use in placental development, akin to the ERVW syncytin. Though much is left to ascertain, the innate immune response to ERVK Env expression has been partially characterized and appears to be due to a region located in the transmembrane domain of the Env protein. In this review, we aim to highlight ERVK Env as a biomarker for inflammatory conditions and explore its use as a future therapeutic target for cancers, HIV infection and neurological disease.